Preferential Effects of the Metabotropic Glutamate 2/3 Receptor Agonist LY379268 on Conditioned Reinstatement versus Primary Reinforcement: Comparison between Cocaine and a Potent Conventional Reinforcer - Baptista, Marco A. S. (J Neurosci, 2004)
Metabotropic glutamate receptors (mGluRs) have been implicated in regulating anxiety, stress responses, and the neurobehavioral effects of psychostimulants. The present study sought to determine whether group II mGluR activation by the potent mGlu2/3 receptor agonist, (–)-2-oxa-4-aminobicylco hexane-4,6-dicarboxylic acid (LY379268), antagonizes reinstatement of cocaine-seeking induced by cocaine-related stimuli and whether this effect extends to behavior induced by stimuli conditioned to a potent conventional reinforcer, sweetened condensed milk (SCM). Also, we tested whether the suppressant effects of LY379268 on conditioned reinstatement extend to the primary reinforcing effects of cocaine or SCM. Rats were trained to associate discriminative stimuli (S(D)) with the availability of cocaine or SCM versus non-reward and then subjected to repeated extinction sessions during which the respective reinforcers and S(D) were withheld. Subsequent reexposure to the cocaine or SCM S(D), but not the non-reward S(D), produced recovery of responding at the previously active lever. LY379268 (0.3–3.0 mg/kg, s.c.) dose-dependently attenuated recovery of cocaine seeking but reduced conditioned reinstatement by the SCM S(D) only at the highest dose. LY379268 did not alter responding reinforced directly by SCM, and only the highest LY379268 dose reduced cocaine self-administration. The results suggest that the effects of LY379268 are selective for behavior maintained by cocaine as opposed to palatable conventional reinforcers. More importantly, the results show that LY379268 suppresses behavior motivated by stimuli conditioned to cocaine or SCM more effectively than consummatory behavior maintained by the unconditioned effects of these substances. As such, the results identify group II mGluRs as a pharmacotherapeutic target for craving and relapse prevention associated with cocaine cue exposure.